Analysis of alternative sewage systems for a teaching and research institution in Rio Verde, Goiás - Alves, Vanessa Petronília; Silva Júnior, Edio Damásio da; Carmo, Devaney Ribeiro do (National Journal of City Management, 2024)
Among basic sanitation services, sewage collection and treatment are important for health. It is the responsibility of collective enterprises to implement and maintain sewage systems within their property. The IFGoiano Rio Verde campus has had little updating of its sewage system over the years and has an old ceramic network and rudimentary pits which contain cracks and degradation and are possibly contaminating the soil. There are some possible alternatives for upgrading the campus sewage system. One of them is to establish a new collection network that will be interconnected to the city’s existing public network. Another option would be to sector sewage into decentralized systems with the joint application of septic tanks and wetlands. Therefore, this work aims to analyze the economic viability of each proposed alternative for adapting the campus’s sewage system, and it was possible to observe that the centralized network is a system with greater user reliability, however, more costly, totaling a execution cost of R 1,849,549.35. The decentralized network is a system that is not yet as popular, but less expensive, totaling an execution cost of R 1,382,480.23. In addition to these values, the centralized network has an estimated operating and maintenance cost of R 13,187,424.57 over 20 years, which makes the choice for this alternative unfeasible, as the operating and maintenance costs of the decentralized network are of R 44,697.60.